Effects of neratinib and combination with irradiation and chemotherapy in head and neck cancer cells. (15th August 2016) - Schneider, S; Thurnher, D; Kadletz, L; Seemann, R; Brunner, M; Kotowski, U; Schmid, R; Lill, C; Heiduschka, G
Abstract : Objective: Prognosis of patients with head and neck squamous cell carcinoma (HNSCC) is still poor. Novel therapeutic approaches are of great interest to improve the effects of radiochemotherapy. We evaluated the effects of tyrosine kinase inhibitor neratinib on HNSCC cell lines CAL27, SCC25 and FaDu as a single agent and in combination with irradiation and chemotherapy. Methods: Effects of neratinib were evaluated in HNSCC cell lines CAL27, SCC25 and FaDu. Effect on cell viability of neratinib and combination with cisplatin and irradiation was measured using CCK‐8 assays and clonogenic assays. Western blot analysis was performed to distinguish the effect on epithelial growth factor receptor and HER2 expression. Apoptosis was evaluated by flow cytometry analysis. Results: Growth inhibition was achieved in all cell lines, whereas combination of cisplatin and neratinib showed greater inhibition than each agent alone. Apoptosis was induced in all cell lines. Combination of neratinib with irradiation or cisplatin showed significantly increased apoptosis. In clonogenic assays, significant growth inhibition was observed in all investigated cell lines. Conclusion: Neratinib, as a single agent or in combination with chemo‐irradiation, may be a promising treatment option for patients with head and neck cancer.